Permian basic volcanism on the NW margin of Gondwana in the Guacamaya Formation, Ciudad Victoria Block, Tamaulipas, Mexico - Apolinar Morales, Blanca Sughey; Ramírez Fernández, Juan Alonso; Jenchen, Uwe; Pichardo Barrón, Yolanda (UANL. Facultad de Ciencias de la Tierra, 2023)
The present work focuses on the study of epiclastic units of the Permian Guacamaya Formation from the Tamatán Group, Cd. Victoria Block, representing the basement in the Huizachal-Peregrina Anticlinorium. The results suggest that deep-sea turbidity currents transported volcanic epiclasts included in the siliciclastic strata. Their geochemical signature indicates an intermediate-basic composition related to an island arc, active during the closure of the Rheic Ocean before the assembly of Pangea. This unit is correlatable with the turbidites and lavas of the Tuzancoa Formation exposed in the Hidalgo state. With these results, we propose the existence of a Permian perigondwanan island arc, just now described.